Open Field Two-Texture Preference Testing Is Not Associated With the Neuropathic Pain-Like Phenotype That Occurs Following Mouse Cervical Contusion Spinal Cord Injury - David A. Jaffe; Megan A. Lyttle; Angelo C. Lepore (Neuroscience Insights)
Development of neuropathic pain (NP) is one of the major complications associated with spinal cord injury (SCI). While well-established methods such as von Frey mechanical and facial grimace testing are often used to assess SCI-induced NP-like behaviors in animal models, these assays have significant limitations, including experimenter bias and long periods of active testing and analysis. To address these challenges, we aimed to develop a novel open field 2-texture preference test (TTPT) to assess NP-like behaviors following unilateral C5 hemicontusion SCI in mice. To do so, we modified the open field apparatus by introducing both a rough and a smooth texture to different portions of the chamber floor based on the hypothesis that the abrasive rough surface would differentially elicit NP-like avoidance behavior. However, at both pre-injury baseline and following SCI, mice spent more time and traveled a greater distance on the rough compared to smooth surface. Additionally, the TTPT did not show any correlation with von Frey or grimace data obtained from the same animals. While this novel test may be able to provide information pertaining to other components of functional outcome, the assay is not associated with the persistent NP-like phenotype that occurs following SCI.